VOLD OG VÆREN: Antropologi og den voldelige relation - Kvist, Camilla (Tidsskriftet Antropologi, 2002)
The article addresses “the violent relation” in an anthropological perspective. This entails descriptions of violent encounters made by both victims of domestic violence and by young offenders. The concepts of being and non-being, subjectivity and objectivity, construction and destruction inform the analysis of the violent relation. The body is the primary locus for an understanding of the possibility and the exertion of violence: its power to victimize. Violence is a way to act on the world and others which institutes a bodily sense of agency and power; that is, it becomes a powerful statement of “self”. The claim of one actor, however, is made at the expence of another, whose subjectivity is affected so severely that it questions its own being in the world, both somatically and experientially.